ALAT BUKTI KETERANGAN SAKSI DALAM PERKARA PIDANA SESUDAH PUTUSAN MAHKAMAH KONSTITUSI No. 65/PUU-VIII/2010 TANGGAL 2 AGUSTUS 2011 - Supriyanta -; Bambang Ali Kusumo (Universitas Slamet Riyadi, 2021)
This study is entitled evidence of witness testimony in criminal cases after the Constitutional Court decision No. 65 / PUU-VIII / 2010, dated August 2, 2011. The background of the problem is that juridically, theoretically, even practically, the evidence for witness testimony is what the witness heard himself, saw himself and experienced himself by mentioning the reasons for his knowledge. However, after the decision of the Constitutional Court No. 65 / PUU-VIII / 2010, there has been a fairly fundamental change because the interpretation of the Constitutional Court on witnesses and evidence of witness testimony includes people who can provide information in the context of investigation, prosecution and trial of a criminal act which he does not always hear himself, he saw for himself and he experienced it himself. The Constitutional Court's decision fundamentally changes the value of proof of witness testimony in criminal cases. The purpose of this research is to examine and describe the evidence of witness testimony in criminal cases and their juridical implications in criminal justice after the Constitutional Court decision No. 65 / PUU-VIII / 2010, dated 2 August 2011. Research method, this type of research is normative juridical research. The nature of the research is descriptive. The type of data used is secondary data. The data collection technique is done by using literature study. The data that has been collected are analyzed juridically qualitative. The result of the research is that after the Constitutional Court decision no. 65 / PUU-VIII / 2010 dated August 2, 2011, there is an expansion of the concept of witness testimony which was originally “a person who can provide information in the context of investigation, prosecution and trial of a crime that he has heard himself, he has seen and experienced himself , which was later expanded to become